Designing Creative Learning Media About Processing of Used Milk Boxes into DIY Art and Craft - Antonius Nicky Kosasih; Listia Natadjaja; Rika Febriani (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Waste materials are things in the environment that can be used or returned into something good and useful. One of the results of used good processing is a work of art, which can be made DIY by all people, both adults and children. Creating or customize DIY art and crafts can be an opportunity and the beginning step for children, particularly teenage children, to develop creativity. Children’s creativity needs to be developed in early age, so that one day they have special skills that will be useful in the future. Seeing their ambitions, children can learn anything autodidactically, because there’s social media that support their activity in finding education and entertainment. Instagram and YouTube can become a learning media that will be used to get public support for a creative movement as example. From Instagram and YouTube, teenagers can get many tutorials for them to follow, so they can understand step by step and practice. On Instagram, teenagers will get basic materials up to the steps of making, reviews from random people about the art works that has been made. Also, Instagram will be the media that share events, challenge, giveaway, etc. which is also good for get public attention. And about YouTube, YouTube will become a back-up platform if the education content duration is too long. It will be great for teenagers as the study’s subject if Instagram and YouTube merge as creative learning media that can bring out creative young generations, that can create what they want, and become whom they want in their future.